Duoplasmatron type molecular carbon ion source. Issue 1 (1st April 2022) - Wada, M; Aki, H; Miyamoto, N
Abstract: An ion source capable of producing molecular ions delivers a beam of impurity dopant for shallow ion implantation of semiconductor device fabrication. Production and transport of low energy molecular ions is indispensable for tabulating fundamental data on plasma-wall interactions that should be used to design a future nuclear fusion reactor. An ion source plasma can produce molecular ions of solid materials by sputtering, while low temperature plasma efficiently transports produced molecular ions to the source extraction hole. A duoplasmatron ion source with the carbon plasma electrode has successfully produced poly-atomic carbon ions up to C6 + . The intermediate electrode has six holes to guide cathode plasma to the carbon anode performing as the plasma electrode. A 1 mm diameter extraction hole is opened at the center of the carbon plasma electrode, where is no direct exposure to the plasma from the cathode region. The ion source maintains a stable discharge with both H2 and Ar as discharge support gas, but works better at lower pressure with Ar. A hydrogen plasma produced molecular ions of hydrocarbons with the mass separated current of C3 H5 + with the intensity comparable to other ion species including atomic, diatomic and triatomic hydrogen ions.